The Expression of Fiscal Decentralization in Lithuania: Increase of Financial Autonomy of Municipalities - Astrauskas, Algirdas; Striškaitė, Jūratė (Ekonomika, 2003)
In recent decades the world saw a growing tendency of decentralization manifesting itself in federal and unitary states as well as developing and developed countries. After the restoration of Lithuania’s independence, decentralization has affected political, administrative and economic systems. A more effective system of public administration has been pursued in the country by way of the development of local municipalities. Within more than a decade of independence in Lithuania municipalities have become stronger and gained a wide range of functions and rights. However, on the level of self-government financial autonomy has been low and fiscal decentralization yet rather poorly developed. The main obstacles to the performance of systems on the level of local self-government and public administration are seen to lie in the present financial situation of municipalities and the low level of fiscal decentralization in the country. The object of this research is fiscal decentralization and the form it assumes in Lithuania as well as the restricted financial autonomy of municipalities. The research aims at elucidating the concept of fiscal decentralization, analysing the present financial situation of municipalities and the way fiscal decentralisation is manifest in Lithuania, corroborating the idea of restricted financial autonomy of municipalities and suggesting ways to improve the present situation. The goal of the present investigation has assumed the following objectives: to explain the conception of fiscal decentralization; to discuss the manifestation of fiscal decentralization in Lithuania and look at the actual financial situation of municipalities from the points of view of their financing of functions. tax revenue. fiscal transfers and borrowing mechanisms; to corroborate the restricted financial autonomy of municipalities in terms of four constituents of fiscal decentralization by taking quantitative and qualitative dimensions as a basis; to produce guidelines as to the ways the financial autonomy of municipalities in Lithuania may be increased with the aim to enhance the performance of local self-government.